If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + -6) = 4(3b + -7) Reorder the terms: 2(-6 + 4x) = 4(3b + -7) (-6 * 2 + 4x * 2) = 4(3b + -7) (-12 + 8x) = 4(3b + -7) Reorder the terms: -12 + 8x = 4(-7 + 3b) -12 + 8x = (-7 * 4 + 3b * 4) -12 + 8x = (-28 + 12b) Solving -12 + 8x = -28 + 12b Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8x = -28 + 12 + 12b Combine like terms: -12 + 12 = 0 0 + 8x = -28 + 12 + 12b 8x = -28 + 12 + 12b Combine like terms: -28 + 12 = -16 8x = -16 + 12b Divide each side by '8'. x = -2 + 1.5b Simplifying x = -2 + 1.5b
| 2x+12+7x=-2 | | 0.04p+0.06(1800-p)=95 | | -420=-7(8n-4) | | 0.05/4000000 | | -6y+9=27 | | 5z-8=6z+1 | | (4x)^-1/2=8 | | -5+15x=14x | | 5(x-4)=-4+5x | | x^2+8x+21=y | | 12.3+5.013d=16.5 | | 15j+120=795 | | 3=5(x-4)+2-4x | | 8x+2=20-2 | | 2xy+6h= | | (2x-3)/6 | | 17=18-1b | | (10x-3y)-(8y+1)= | | -3+-18r=-345 | | 5x^2+6y+1=0 | | 3(1+6r)=-87 | | 4x+2x+56=180 | | -(2-3p)=p-18 | | 36=8z+20 | | 7/8*2 | | .291666= | | 0.03p+0.05(1300-p)=75 | | 3/x-3×5/2x-6=11/2 | | 3/9=y/12 | | (X+1+2i)(x+1+2i)=0 | | -3r+8+5r+-1= | | 5+2z=2z+6 |